Lexical Cohesion Markers in Digest Magazine October 2021 issue - Ni Nyoman Sarmi; Sri Wahyuni (Formosa Journal of Multidisciplinary Research, 2023)
The culmination of this research is examining various markers of lexical cohesion in the October 2021 issue of Intisari magazine. The various types of writings in the magazine have a mission to provide enlightening information for the readers. The coverage of Intisari magazine is quite broad and in-depth—covering history, geography, and tradition—allowing it to be more complete and interesting to study. Starting from aspects of form, vocabulary, sentences, inter-sentence connections, and sentence structure. This is the basis why researchers take the essence as the object of study. In his analysis, the researcher uses the Sumarlam concept as a reference for the classification of lexical cohesion markers in discourse. This study uses a qualitative descriptive method with the October 2021 edition of Intisari magazine as the object of study. The data collection method used literature study with analytical descriptive technique as a data analysis technique. The results of the study showed various markers of lexical cohesion, including: (i) repetition, (ii) synonymy, (iii) antonymy, (iv) hyponymy, (v) collocation, and (vi) equivalence. Variations in the use of lexical cohesion in Intisari magazine are a form of applying the types of lexical cohesion markers in discourse.